2015
DOI: 10.1111/jtxs.12129
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Tomatoes Subjected to an Induced Compression during Storage

Abstract: The purpose of this work was to evaluate texture alterations due to compression load on tomatoes stored at 15 and 25C, which simulates transport in type "K" wooden boxes. The following mechanical properties were analyzed during storage: firmness, proportional deformity modulus, energy to deform the product, penetration force of the tomato skin and the energy required for penetration. Structural alterations were noticed solely by a puncture test. The mechanical property values significantly decreased during sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
1
9
1
Order By: Relevance
“…Oliveira, Corrêa, Botelho and Oliveira (2015) reported that the firmness of tomato fruit can vary from 34.68 to 21.24 N, while the result from this paper shows which was between 45 and 10 N during storage time. The decrease of tomato firmness during storage period was reported by several researchers (Oliveira et al, 2015;Schouten et al, 2014Schouten et al, , 2007. The result of this paper can help to study the structural hardness of tomato fruit during the storage period.…”
Section: Fractional and Polynomial Modelcontrasting
confidence: 52%
See 1 more Smart Citation
“…Oliveira, Corrêa, Botelho and Oliveira (2015) reported that the firmness of tomato fruit can vary from 34.68 to 21.24 N, while the result from this paper shows which was between 45 and 10 N during storage time. The decrease of tomato firmness during storage period was reported by several researchers (Oliveira et al, 2015;Schouten et al, 2014Schouten et al, , 2007. The result of this paper can help to study the structural hardness of tomato fruit during the storage period.…”
Section: Fractional and Polynomial Modelcontrasting
confidence: 52%
“…A decrease in the firmness during storage period, which caused by breakdown of the tomato fruit cell structure (Schouten et al, 2007). Oliveira, Corrêa, Botelho and Oliveira (2015) reported that the firmness of tomato fruit can vary from 34.68 to 21.24 N, while the result from this paper shows which was between 45 and 10 N during storage time. The decrease of tomato firmness during storage period was reported by several researchers (Oliveira et al, 2015;Schouten et al, 2014Schouten et al, , 2007.…”
Section: Fractional and Polynomial Modelmentioning
confidence: 54%
“…Since 2002, many research articles on texture of raw or minimum processed vegetables and fruits have been published in the JTS . New methods for precise evaluation of vegetables and fruits were proposed (Barikloo & Ahmadi, ; Boonmung, Chomtee, & Kanlayasiri, ; Camps, Guillermin, Mauget, & Bertrand, ; Dan et al, ; De Oliveira, Corrêa, Botelho, & De Oliveira, ; Desmet, Lammertyn, Verlinden, & Nicolaï, ; Kabas & Ozmerzi, ; Lana, Tijskens, De Theije, Dekker, & Barrett, ; Maury et al, ; Park, Chun, Lee, Lee, & Kim, ; Puangsombut, Pathaveerat, Terdwongworakul, & Puangsombut, ; Solomon & Jindal, ; Terdwongworakul, Puangsombat, & Pathaveerat, ; Trnka, Pavloušek, Medomoca, & Buchar, ; Valero et al, ; Vandenberghe & Claes, ; Vincent, Saunders, & Beyts, ). A specified part of vegetable and fruits, such as single cells from tomato pericarp (Wang, Pritchard, & Thomas, ), cell walls of carrot and potato (Zdunek & Umeda, ), carrot cell walls (Kurita & Masuda, ), epidermal tissue of onion (Hepworth & Bruce, ), and kiwi peelability (Harker, Hallett, White, & Seal, ) were also investigated.…”
Section: Texture Evaluations Of Heterogeneous Vegetables and Fruitsmentioning
confidence: 99%
“…The factors affecting the quality of blueberries mainly include three parts: (a) during the process of grading and packaging, blueberries are constantly impacted and squeezed (Moggia, Graell, Lara, González, & Lobos, 2017; Prusky, 2011; Zhang, Yang, Meng, Liu, & Kou, 2011); (b) changes in external temperature, humidity, etc. (de Oliveira, Correa, Botelho, & de Oliveira, 2015; Ghodki et al, 2020; Stropek & Gołacki, 2013); and (c) the fruit continues to mature. The mechanical damage to blueberries mainly includes two parts: compression and impact damage.…”
Section: Introductionmentioning
confidence: 99%